Descriptive study on the level of OSH awareness among UiTM Cawangan Pulau Pinang staff / Rosley Jaafar ... [et al.] - Jaafar, Rosley; Umar, Norazah; Ibrahim, Anas; Razali, Wan Noorli (Universiti Teknologi MARA, Perlis, 2022)
Safety and health are important factors of any organization to ensure smooth and effective functioning. Occupational safety and health (OSH) awareness among the workers in the prevention of occupational injuries and illness. Various programmes have been implemented by the government and private organizations to increase the knowledge and awareness of OSH in the workplace including among institution higher learning staff in Malaysia. A study was undertaken to identify factors influencing the awareness level of OSH among the staff of Universiti Teknologi MARA (UiTM) in Pulau Pinang Malaysia. A self-administered online questionnaire was distributed to the staff through UiTM email and 193 staff had responded. The questionnaire covered 43 questions and was divided into seven (7) factors that influence awareness levels. The data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 20 and presented in descriptive statistics. The study revealed that the highest level of awareness factor was OSH policy with a mean score of 4.90 while the lowest level factor was safety and health committee with a mean score of 3.90. The analysis of all factors indicated that non-academic staff awareness of OSH is higher than academic staff with a mean score of 4.51 and 4.41 respectively. The university management should increase the role of the safety and health committee so that it can conduct more safety and health activities such as safety talks, training, and campaign through posters and signage on the campus. Good OSH management is very important to prevent an accident in the workplace towards the development of a safe culture.